Competency Development in Improving Mine Inspector Performance - Yoga Pratama; Yoke Pribadi Kornarius (Publikasi Indonesia, 2023)
National mineral and coal mining is the most crucial part of supporting non-tax state revenue (PNBP) in Indonesia. Mining Inspectors (IT) in Indonesia play a very crucial role in ensuring proper and correct mining activities management. The position of Mining Inspector has Competency Standards, formal education, work experience, and attitudes that have been regulated by the government. So far, there has been no research conducted to answer the question of whether the competencies possessed by each Mining Inspector can improve the performance of supervision in mineral and coal mining engineering and environmental aspects. This research was conducted on all Mining Inspectors in Java and Sumatra using a saturated sample. The data was then processed using SmartPLS data processing software. It was revealed in this research that Formal Education, Work Experience, and Competency Development have a positive and significant influence on Organizational Performance. Competency Development can act as a mediator of the influence of the two exogenous variables on Organizational Performance. Through these findings, stakeholders are expected to design programs to improve formal education, work experience, and the competencies of Mining Inspectors.